Daya Tahan Hidup Fragmen Koloni Rayap Tanah Coptotermes curvignathus Holmgren (Isoptera: Rhinotermitidae) dalam Pemeliharaan di Laboratorium - Kutana, Agung Nugrawan; Nandika, Dodi; Arinana; Hanifah, Nisrina Putri; Wahyuningtias, Irma (Forestry Faculty of Hasanuddin University, 2024)
Information about colony fragments survival of the termite species Coptotermes curvignathus Holmgren in the laboratory is very limited. This study was conducted to determine colony fragments survival of the subterranean termite C. curvignathus Holmgren in laboratory maintenance. The test media used the Termitarium PSIH-IPB: 1999 as a glass vessel containing 4 kg of a mixture of sand and clay with 4 proportions and 4 different pH determined as treatments that would be studied for their effects on termite survival. The results showed that the proportion of the sand:clay mixture affected the survival and feeding preferences of the subterranean termite C. curvignathus Holmgren. The highest percentage of termites that survived was found in the termitarium containing a mixture of sand:clay 50:50. The highest percentage of bait wood weight loss occurred in the test media containing a mixture of sand: clay 50:50. The weight loss of bait wood is directly proportional to the termites survival.